The Fungi: 1, 2, 3 ... 5.1 million species? - Blackwell, Meredith (American journal of botany, 2011)
Premise of the study: Fungi are major decomposers in certain ecosystems and essential associates of many organisms. They provide enzymes and drugs and serve as experimental organisms. In 1991, a landmark paper estimated that there are 1.5 million fungi on the Earth. Because only 70000 fungi had been described at that time, the estimate has been the impetus to search for previously unknown fungi. Fungal habitats include soil, water, and organisms that may harbor large numbers of understudied fungi, estimated to outnumber plants by at least 6 to 1. More recent estimates based on high-throughput sequencing methods suggest that as many as 5.1 million fungal species exist. Methods: Technological advances make it possible to apply molecular methods to develop a stable classification and to discover and identify fungal taxa. Key results: Molecular methods have dramatically increased our knowledge of Fungi in less than 20 years, revealing a monophyletic kingdom and increased diversity among early-diverging lineages. Mycologists are making significant advances in species discovery, but many fungi remain to be discovered. Conclusions: Fungi are essential to the survival of many groups of organisms with which they form associations. They also attract attention as predators of invertebrate animals, pathogens of potatoes and rice and humans and bats, killers of frogs and crayfish, producers of secondary metabolites to lower cholesterol, and subjects of prize-winning research. Molecular tools in use and under development can be used to discover the world's unknown fungi in less than 1000 years predicted at current new species acquisition rates.